1995
DOI: 10.1007/bf00964127
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function during a prolonged stay in Antarctica

Abstract: Adaptation of the thyroid gland to the Antarctic environment was studied in nine healthy euthyroid tropical men of the Sixth Indian Antarctic Expedition during 1 year of their residence at polar latitudes. Circulatory concentrations of thyroid hormones, total T4 (TT4), total T3 (TT3), free T4 (FT4), free T3 (FT3), reverse T3 (rT3), thyroxine binding globulin (TBG), T3 uptake and thyroid stimulating hormone (TSH) were estimated in New Delhi and during the first week of each month of the stay in Antarctica. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…While the monthly studies did not reveal changes in the FT 3 and FT 4 levels during wintering, the authors have suggested that the serum TH levels during Antarctic wintering were affected by various factors of which the physical activity and the sharp change of day duration were the most significant. The TSH concentrations in March, April, November and December were found to be significantly higher than before wintering [21]. These data testify on our opinion about an important role of ethnic origin of the examined groups.…”
Section: Discussionsupporting
confidence: 83%
“…While the monthly studies did not reveal changes in the FT 3 and FT 4 levels during wintering, the authors have suggested that the serum TH levels during Antarctic wintering were affected by various factors of which the physical activity and the sharp change of day duration were the most significant. The TSH concentrations in March, April, November and December were found to be significantly higher than before wintering [21]. These data testify on our opinion about an important role of ethnic origin of the examined groups.…”
Section: Discussionsupporting
confidence: 83%
“…*P < 0.05, Great Wall Station versus Zhongshan Station Palinkas et al 2007a;Levy et al 2013), FT4 of the Zhongshan Station crew decreased during the austral winter. Concurrently, TSH levels increased gradually until return to China, where they became statistically significant, suggesting the presence of Polar T3 Syndrome (Sawhney et al 1995;Do et al 2004). The declining levels of FT3 and FT4 prompt the hypothalamic-pituitary-thyroid (HPT) axis to produce more TSH to stimulate the increased availability of these two hormones.…”
Section: Discussionmentioning
confidence: 94%
“…There are cases of humans with partial or total TBG deficiency, which results in euthyroid hypothyroxinemia (Refetoff 1989, Bartalena 1993. Even though exposure to cold is known to induce alteration in thyroid hormone metabolism in humans (Solter et al 1989, Sawhney et al 1995, Do et al 2004, to the best of our knowledge there are no reports on the ability of these individuals to adapt to cold. Because TTR-null mice are also euthyroid hypothyroxinemic, it is reasonable to believe that humans with TBG deficiency would normally adapt to cold.…”
Section: Figurementioning
confidence: 99%